Comprehensive risk management using fuzzy FMEA and MCDA techniques in highway construction projects. Issue 2 (17th February 2017) - Ahmadi, Mohsen; Behzadian, Kourosh; Ardeshir, Abdollah; Kapelan, Zoran
Abstract: This paper presents a comprehensive framework to manage the main risk events of highway construction projects within three stages: (1) identification of potential risks; (2) assessment and prioritisation of identified risks based on fuzzy FMEA; (3) identification of appropriate response. The main criteria analysed for prioritising potential risk events are cost, time and quality which are quantified and combined using fuzzy AHP. A new expert system is suggested for identifying an appropriate risk response strategy for a risk event based on risk factor, control number and risk allocation. The best response action for a risk event is then identified with respect to the same criteria using "scope expected deviation" (SED) index. The proposed methodology is demonstrated for management of risk events in a construction project of Bijar-Zanjan highway in Iran. For the risk event of "increase in tar price", deviation from the target values of the criteria is analysed for business-as-usual state plus two risk response actions using SED index. The results show that the response action of "changing paving construction technology from asphalt pavement to RCC pavement" can successfully cope with the risk event of "increase in tar price" and have the minimum deviation.